Når unge begår vold - Maria Libak Pedersen (Nordisk Tidsskrift for Kriminalvidenskab)
This article examines violent youth cultures in socially disadvantaged residential areas in Denmark. The focus on these cultures stems from their identification by youth themselves when describing the local circumstances that contribute to their repeated involvement in violence. The tone among these young people is harsh and they seem to believe that an aggressive behaviour pattern is necessary for their own survival. Violent behaviour is expected and these expectations are difficult to counteract given the conventionality of violence within the culture. In that sense, the culture works to further reinforce the marginalization of these already marginalised youth. The article focuses on neighbourhood conditions and the social codes found among young people on the street. The stories they tell about the violence they have committed and the reality they experience depicts a particularly violent youth culture context.